Effect of Flow Field on Surface Slag Entrainment and Inclusion Adsorption in a Continuous Casting Mold. Issue 2 (29th November 2019) - Zhang, Kai-Tian; Liu, Jian-Hua; Cui, Heng
Abstract : A water model of slab mold was established to analyze the flow field behaviors. Particle image velocimetry measurement, fluctuation sensors, and industrial experiments were adopted to analyze the slag entrainment and inclusion adsorption. The risk of surface slag entrainment was discussed from the perspectives of flow patterns, surface fluctuation, and velocity. The ability of mold slag to adsorb inclusions was discussed by electrolysis on slab samples. The results reflected that the flow field determined the fluctuated amplitude, surface pattern and flow velocity of the mold surface, playing an important role in the slag entrainment and inclusion adsorption. Uneven surface fluctuations and downward vertical velocity lead to high slag entrapping risk. High surface horizontal velocity in mold leads to a higher inclusion concentration gradient at the slag‐steel interface, which leads to a stronger ability of mold slag to adsorb inclusions. Abstract : A water model of a slab mold is established to analyze the flow field behaviors. The results reflect that uneven surface fluctuations and downward vertical velocity lead to high slag‐entrapping risk. High surface horizontal velocity leads to a higher inclusion concentration gradient at the slag–steel interface, which leads to a stronger ability of the mold slag to adsorb inclusions.